The effect of two commonly consumed energy drinks on the bond strength of conventional and APC® brackets - Saya Mustafa Azeez; Omar Fawzi Chawshli (Erbil Dental Journal)
Background and Objective: One of the common problems during orthodontic treatment is a bond failure, which interferes with treatment course and results in increased treatment duration and more clinical time for rebonding of failed brackets. This study aimed to determine the effect of energy drinks on the shear bond strength and adhesive remnant index on two types of orthodontic metal brackets.